2012
DOI: 10.1017/jfm.2012.136
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic and thermodiffusive instability effects on the evolution of laminar planar lean premixed hydrogen flames

Abstract: Numerical simulations with single-step chemistry and detailed transport are used to study premixed hydrogen/air flames in two-dimensional channel-like domains with periodic boundary conditions along the horizontal boundaries as a function of the domain height. Both unity Lewis number, where only hydrodynamic instability appears, and subunity Lewis number, where the flame propagation is strongly affected by the combined effect of hydrodynamic and thermodiffusive instabilities are considered. The simulations aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 61 publications
11
36
0
Order By: Relevance
“…A general hydrodynamic theory of flames pertaining to low-Mach-number flows was presented by Matalon & Matkowsky (1982). As the resulting system, consisting of the Euler equations governing the flow coupled with a flame-front equation, is highly nonlinear, numerical solutions appeared only recently (Helenbrook & Law 1999;Rastigejev & Matalon 2006;Creta & Matalon 2011;Altantzis et al 2012). It has been found that a slightly perturbed flat flame develops wrinkles owing to DL instability.…”
Section: R C Assier and X Wumentioning
confidence: 99%
“…A general hydrodynamic theory of flames pertaining to low-Mach-number flows was presented by Matalon & Matkowsky (1982). As the resulting system, consisting of the Euler equations governing the flow coupled with a flame-front equation, is highly nonlinear, numerical solutions appeared only recently (Helenbrook & Law 1999;Rastigejev & Matalon 2006;Creta & Matalon 2011;Altantzis et al 2012). It has been found that a slightly perturbed flat flame develops wrinkles owing to DL instability.…”
Section: R C Assier and X Wumentioning
confidence: 99%
“…[10] and [11]). The other 77 method is to use non-unity Lewis number (e.g., [12]). Altantzis et al [12] investigated the effect 78 of hydrodynamic and diffusive-thermal instabilities in lean premixed hydrogen/air planar 79 flames using DNS and utilizing a one-step global reaction model.…”
mentioning
confidence: 99%
“…To 95 exclude the effects of thermal-diffusive instability, they assumed the Lewis number is unity. [12]. The governing equations are solved using detailed transport to investigate the effects of …”
mentioning
confidence: 99%
See 2 more Smart Citations